MEASUREMENT OF FE AND MN CONCENTRATIONS BASED ON IMAGE PROCESSING TECHNIQUES USING COLOR INTENSITY MEASUREMENT APPROACH - Sandi Daniar, Putri
Water quality monitoring is the first step to create environmental quality with clean and healthy water sources. Various monitoring methods that are generally used such as spectrometry-based instruments certainly have various limitations, such as expensive costs, requiring a lot of reagents, sensitive instruments to the environment so that the process must be carried out in the laboratory, and takes quite a long to get measurement results. Along with the development of population growth and the increasing water pollutant, water quality monitoring technology that could be operated easily, cheap, practical, quick and accurate is important to be made. Therefore, this research is about to develope a water quality monitoring method based on multiparameter image processing techniques. This method utilizes the approach of color intensity, light, and number/size/shape of particles. This research will be focus on measuring iron (Fe) and manganese (Mn) concentrations using color intensity approach using Plugable Digital Viewer, ColorSlurp and Microsoft Excel software by the image RGB (Red, Green, Blue) matrix as measurement values. The correlation between parameter concentration and color intensity obtained by transforming RGB into 1/GI values. The linear response of the calibration curve was observed in the Fe concentration range from 0 to 2.4 mg/L with the highest correlation R2 = 0.971, and in the Mn concentration range between 0 to 1.6 mg/L with the highest correlation R2 = 0.9432. The measurement of Fe and Mn concentrations in surface water samples using image processing techniques provides similar result as measurements using a UV-Vis spectrophotometer, because there is no significant difference where the p-value obtained is >0.05 at 95 % confidence level. This research found that image processing techniques can be used as an effective, reliable and easy to use method of measuring Fe and Mn concentrations.